Digital Media and Grassroots Anti-Corruption (Edward Elgar Publishing, 2024)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Delving into a burgeoning field of research, this enlightening book utilises case studies from across the globe to explore how digital media is used at the grassroots level to combat corruption. Bringing together an impressive range of experts, Alice Mattoni deftly assesses the design, creation and use of a wide range of anti-corruption technologies.